2021
DOI: 10.1172/jci149236
|View full text |Cite
|
Sign up to set email alerts
|

Group IIA secreted phospholipase A2 is associated with the pathobiology leading to COVID-19 mortality

Abstract: There is an urgent need to identify cellular/molecular mechanisms responsible for severe COVID-19 progressing to mortality. We initially performed untargeted/targeted lipidomics and focused biochemistry on 127 plasma samples and found elevated metabolites associated with secreted phospholipase A2 (sPLA2) activity and mitochondrial dysfunction in severe COVID-19 patients.Deceased COVID-19 patients had higher levels of circulating, catalytically active sPLA2 Group IIA (sPLA2-IIA), with a median value 9.6-fold hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 48 publications
10
82
0
4
Order By: Relevance
“…SP-A, via its ability to inhibit surfactant phospholipid hydrolysis and thus maintain, to a certain extent a well-functioning surfactant, plays a protective role in lung injury. This is of great relevance to the current Covid-19 pandemic, as sPLA2-IIA was shown to associate with markers more likely to lead to mortality after SARS-CoV-2 infection (63).…”
Section: Surfactant-related Activitiesmentioning
confidence: 90%
“…SP-A, via its ability to inhibit surfactant phospholipid hydrolysis and thus maintain, to a certain extent a well-functioning surfactant, plays a protective role in lung injury. This is of great relevance to the current Covid-19 pandemic, as sPLA2-IIA was shown to associate with markers more likely to lead to mortality after SARS-CoV-2 infection (63).…”
Section: Surfactant-related Activitiesmentioning
confidence: 90%
“…Recent data has highlighted a new link between hGIIA and SARS-CoV-2 infection during the COVID-19 pandemic [ 97 ]. Out of 80 clinical indices measured, including age and body mass index, hGIIA and blood urea nitrogen (BUN) were the strongest predictors of severe disease, with a decision tree based on these two indicators being able to stratify patients with mild severe or fatal infection on a validation cohort of COVID-positive patients.…”
Section: Hgiia Functionmentioning
confidence: 99%
“…Out of 80 clinical indices measured, including age and body mass index, hGIIA and blood urea nitrogen (BUN) were the strongest predictors of severe disease, with a decision tree based on these two indicators being able to stratify patients with mild severe or fatal infection on a validation cohort of COVID-positive patients. Sars-CoV-2 infection also alters the lipidome, resulting in higher concentrations of lyso-PE and lyso-PS, with no changes in lyso-PC, which is a hallmark of hGIIA activity [ 97 ]. Other research suggests COVID-19 may also increase levels of PS on the surface of the cell membrane, exposing cells to catalytic activity of hGIIA [ 97 , 98 ].…”
Section: Hgiia Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under infectious and inflammatory conditions, sPLA 2 -IIA expression is highly induced in numerous cell types, including endothelial, hepatic, renal, smooth muscle, macrophages, mast cells, platelets, astrocytes, and glial cells (34,45,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The serum concentration of sPLA 2 -IIA can increase up to 1000fold during sepsis, to reach concentrations of ~5 μg/mL (~350 nM) (64), and recent studies revealed that it is also induced in COVID-19 patients (65). Investigation of the gene promoter revealed that sPLA 2 -IIA is induced by proinflammatory cytokines such as IL-1β, IL-6, and TNF-α (66-69), while activation of TLR and nucleotide-binding oligomerization domain-like receptors (NLR) by pathogen-associated molecular patterns (PAMPs) also trigger sPLA 2 -IIA expression through the NF-κB pathway (70)(71)(72)(73)(74).…”
Section: Introductionmentioning
confidence: 99%